The effects of Gratitude, Spiritual Intelligence, and Organizational Citizenship behavior on Speaker performance: A case study of higher education in Lubuklinggau town - Triono; Nopa Dwi Saputra; Anurag Hazarika; Sabeeha Hamza Dehham (Istithmar, 2023)
This study aims to determine the influence of Gratitude, spiritual intelligence, and Organizational Citizenship Behavior (OCB) on the performance of lecturers at universities in Lubuklinggau, South Sumatra. This study used a quantitative approach. Data analysis was carried out using SPSS version 24. The sample used in this study was 99 respondents. The results showed that Gratitude had a partial effect on lecturer performance, the results of the t-test showed a calculated t value more significant than the tablet (2.477 > 1.984) and a significance value of 0.002; Spiritual Intelligence partially affects the performance of lecturers, the results of the t-test show a calculated t value more significant than the tablet (3.667 > 1.984) and a significance value of 0.001; OCB has a partial effect on lecturer performance, the results of the t-test show a calculated t value more significant than the tablet (2.889 > 1.984) and a significance value of 0.000; Furthermore, Gratitude, Spiritual Intelligence, and OCB together (simultaneously) affect lecturer performance, where the calculated f value is greater than the table f (26,997 > 2,696).